Wpływ opadów atmosferycznych i temperatury powietrza na wahania stanów wód gruntowych w profilu Buk - Skórzewo - Poznań-Szczepankowo w latach 1961-1983 - Nowak, Anna (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2007)
This study depicts analysis results of influence of precipitation and air temperature on fluctuation of the level of the groundwater table in Buk – Skórzewo – Poznań-Szczepankowo profile in years 1961–1983. It is assumed in this work, that the level first groundwater table primarily depends on meteorological conditions, however local conditions, as relief, geology, etc. have minor influence. Therefore chosen observation posts characterize comparable conditions of aquifer occurrence (similar geomorphology, petrology). In this study foregoing data were used: groundwater table, daily precipitation and average daily air temperature from the period 1961 to 1983. A groundwater table was measured in three stations: Buk (52°21’ N, 16°32’ E), Skórzewo (52°23’ N, 16°48’ E) and Poznań-Szczepankowo (52°22’ N, 17°01’ E). However meteorological data originate from Poznañ-£awica (52°25’ N, 16°50’ E) station, which was chosen as a representative. On the basis analysis of variability of groundwater level and distribution of precipitation and air temperature in years 1961–1983, as well as correlation analysis, some mutualdependences between mentioned hydroclimatological elements can be affirmed. On the basis of variability of average annual level of the groundwater table (approximate to three analyzed posts) and annual precipitation, the relationship between both elements has been found out: along with increasing precipitation groundwater table rises up. However analysis of the correlation matrix can affirm, that precipitation in July and December have a largest impact on groundwater table. Moreover, usually the correlation coefficient takes a highest value for precipitation in relevant month and groundwater table in successive one, which could prove of one-month delaying factor during groundwater recharge or bailing. Despite confirmed relationship between meteorological conditions and fluctuations of groundwater level, there is still need of such studies. Kind and intensity of precipitation seems to be an important factor for groundwater recharge and renewal mechanisms. The above could help in creating mathematical models and prediction of quantity and quality of groundwater.